2020
DOI: 10.1590/0104-1428.03120
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between stress relaxation behavior and thermal stability of natural rubber vulcanizates

Abstract: It is well-recognized that different sulphur curing systems have greatly influenced to the final properties of the rubber vulcanizates. In this study, the properties of vulcanizates with conventional vulcanization (CV) and efficiency vulcanization (EV) systems were correlated in the aspect of stress relaxation and thermal stability. The stress relaxation behaviour and thermal stability were studied with the temperature scanning stress relaxation (TSSR) and with thermogravimatric analysis (TGA) techniques, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…31 The thermal stability of all NR vulcanizate samples was estimated from the temperature at which the sample had lost 5% of its initial weight (T d5 ). 32 The T d5 of the NR shifted from ∼286°C to ∼334-338°C (by about 17-18%) for cyclized NR, depending on the degree of cyclization. In addition, the degradation of the NR shifted toward a higher temperature with increasing cyclization level in the entire tested range.…”
Section: Resultsmentioning
confidence: 94%
“…31 The thermal stability of all NR vulcanizate samples was estimated from the temperature at which the sample had lost 5% of its initial weight (T d5 ). 32 The T d5 of the NR shifted from ∼286°C to ∼334-338°C (by about 17-18%) for cyclized NR, depending on the degree of cyclization. In addition, the degradation of the NR shifted toward a higher temperature with increasing cyclization level in the entire tested range.…”
Section: Resultsmentioning
confidence: 94%
“…On the other hand, the highest content of monosulfidic crosslinks in the vulcanizates obtained using EV facilitated their thermal stability compared to those with SEV and CV. It was due to the high thermal stability of monosulfidic linkages, which may retard both the scission of crosslinks and degradation of the elastomer main chain during decomposition 46,47 . Thus, it was concluded that both, the type of accelerator used, that is, the thermal stability of the accelerator, and the structure and content of the crosslinks in the elastomer network considerably affected the thermal stability of the vulcanizates.…”
Section: Resultsmentioning
confidence: 99%
“…The unfilled NR compound also showed two degradation regions with an initial weight loss of volatile substances including stearic acid and moisture at 200°CÀ280°C, and a major weight loss related to the degradation of NR molecules at 350°CÀ465°C. 47 The T onset , T end set , and char residue of the NR vulcanizate were 353.8°C, 461.2°C, and 3.3%, respectively. From Figure 7(c) and (d), the DTG curves showed T max of WBL, FL, and NR compound at 331.5°C, 341°C, and 384.3°C, respectively.…”
Section: Tga Analysismentioning
confidence: 93%